UgandaInfo - Uganda Bureau of Statistics (Kampala : Uganda Bureau of Statistics, 2011)
UgandaInfo is a socio-economic database system consisting of key ind icators for monitoring progress towards poverty eradication and social development, in general. UgandaInfo has been developed to provide the Government of Uganda and its development partners with comprehensive, official, timely and reliable national data for policy development, pla nning and monitoring in a user-friendly manner
Sponsored by the Republic of Uganda in collaboration with UNICEF.
System requirements: 128 MB of RAM
300 MB of free hard disk space.
Display resolution 640 x 480 (1024 x 768 or higher recommended)
Microsoft Windows 95 or above
Microsoft Office 97 or above
Keywords: Databases -- Uganda